ANALYSIS OF PROFITABILITY AND COMPANY SIZE ON DIVIDEND POLICY - Bayu Adi; As’adur Rofik; Sheli Rachmawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The goal of is to investigate the relationship between dividend policy and company size on profitability. The research sample is the financial reports of several companies during the observation period. Data analysis through SPSS multiple linear regression analysis. Research findings prove dividend policy has a positive significant impact on profitability. The idea that net income serves as the primary basis for determining dividend distribution is supported by these findings. On the other hand, company size has no visible impact on dividend policy. Although it is generally believed that larger companies have more stable operations it is not always a primary consideration when determining dividend policy. This proves that a company's profit-creating ability has a greater affect on dividend distribution decisions than the size of its total assets. Therefore, profitability has a greater influence than company size.